RANCANG BANGUN ALAT BIO KOMPOSTER DIGESTER - Santhiarsa, I.G.N.N.; Suryada, I.G.B.; Wijaya, I.K. (Buletin Udayana Mengabdi, 2017)
environmentally friendly business Garbage Bank Asri Karya and Sesetan Lestari. Both of these efforts have essentially the same problems, namely with regard to productivity and efficiency due to sewage treatment process, especially organic waste which is still conventional and thus require relatively more energy, time and place. Based on these descriptions, as well as in efforts to overcome the existing problems, the objectives and outcomes of activities designed to produce innovation is a versatile organic waste processing equipment that could be as a garbage composter and digester that can be operated with productivity 3-4 times compared to conventional means. Biocomposter digester tool is composed of three main parts, the basic part, the part that holds the leachate result of the process of decomposition of garbage, will be used as a liquid fertilizer, the middle section, a space is laid solid waste, in this part of the garbage is processed into solid fertilizer and also to produce biogas. Then the upper part, the part that holds temporary biogas results from the garbage fermentation process.